Recovery Of Phosphate From Livestock/Aqueous Wastewater Using Struvite Crystallization - Foo, Jia Qi (2020)
Phosphate (PO4 3−) from intensively discharge of livestock wastewater to water bodies leads to various environmental problems especially eutrophication. Besides, phosphate rock which is mainly used for plant fertilizer is a non-renewable resource which is depleting in the next century. It is thus important to seek for a technology that is not only able to effectively remove phosphate but also recover it from the wastewater discharged. Struvite crystallization is one of the methods to recycle phosphate from wastewater into a crystallize product, namely magnesium ammonium phosphate (known as struvite). It is a slow release fertilizer that can be effectively taken up by plant, thereby reducing the phosphate from mining. In order to achieve optimum phosphate recovery via struvite crystallization, it is important to study the effects of the major parameters that give significant impacts on the process, including pH, Mg: P molar ratio and precipitation time. Synthetic livestock wastewater as pure system was applied to investigate the effects of these parameters. Eventually, the optimum parameter conditions would be applied to the actual livestock wastewater to evaluate the feasibility of struvite crystallization in practical condition. Furthermore, kinetics study and solids analysis were carried out to determine the crystal growth rate and impact of parameters on solid crystals. The results showed that the phosphate recovery efficiency of struvite crystallization was excellence at alkaline condition of pH 10. With higher molar concentration of Mg2+ provided, the solution reached supersaturation state and achieved higher phosphate recovery efficiency. It was found that the precipitation time of 60 minutes was required to reach equilibrium. In terms of maximum phosphate recovery, the efficiency in synthetic wastewater was 84.18 %, as opposed to actual livestock wastewater which was only 47.62 %. Solids analysis showed that co-precipitation might occur, which influenced the struvite formation. However, the feasibility study confirmed that struvite crystallization was considered as promising technologies for phosphate recovery for livestock wastewater from the perspective of economics and green chemistry.